Pengaruh Metode Pembelajaran Eksperimen terhadap Hasil Belajar Ilmu Pengetahuan Alam Madrasah Ibtidaiyah Nurul Ihsan - Saidah, Chaira; Sari, Andini Puspita (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
The background of this research is because science learning in MI is still lacking in conducting experiments and involving students to conduct experiments directly. According to Patta Bundu (1986: 5) says that the low learning of science is caused by the teaching of science facts through the lecture method and the lack of opportunities given to students to master science concepts in a higher cognitive domain. In science learning, teachers must involve students more directly or provide opportunities for students to conduct experiments or trials so that students can be fully involved in an experiment or experiment in learning (Wirdawati). With this background, resereachers are interested in examining whether there is an effect of experimental learning methods on students’ science learning outcomes. This research was conducted at MI Nurul Ihsan Segog, Cibening Village, Pamijahan District, Bogor Regency. The population is 136 and the sample is 21 grade IV MI Nurul Ihsan students. The technique of collecting data is through distributing questionnaires and grade IV student report cards at MI Nurul Ihsan Segog. This study uses data analysis techniques descriptive statistics and inferential statistics. From the descriptive statistical data the results of the data analysis of the two variables are categorized with a very good average. While testing the hypothesis using inferential statistics. This analysis technique uses Pearson's Product Moment, namely to determine the relationship between 2 variables (variables X and Y) on an interval scale (a scale that uses actual numbers) (Jakni, 2016). The results of the hypothesis test found that the value of r_count (r_xy) was 0.791 and the value of r_table with N-2 = 21-2 = 19 and a 95% confidence interval was 0.456. So it can be concluded that r_count>r_table or 0.791> 0.456 means that Ha is accepted and Ho is rejected. So in conclusion, there is an influence of experimental learning methods on science learning outcomes in class IV MI Nurul Ihsan Segog. The influence of these two variables based on benchmarks is categorized as high with an average experimental learning method of 89.49 and control science learning outcomes of 83.76. Keywords: Science Learning Outcomes, Experimental Learning Methods, Influence